(untitled) - Fitzgerald, C. P. (London, 1972)
Contents: A history of the expansion and recession of Chinese influence in Yunnan and all of Southeast Asia, resulting in massive immigration of Chinese into these areas. Economic, cultural, and political effects of this migration is studied
Keywords: China,Trung Quốc; Relations,Quan hệ; Đông Nam Á; Southeast Asia